Вознесенная грехом: роман / Кора Рейли - Рейли Кора (Love&Mafia, 2023)
Экземпляры: аб. ЦБ (20240603) / Инвентарный номер: 21442 / Цена: / Сис.шифр: 84(7Сое) / Авт.знак: Р 35 / ГРНТИ: 17.82 / ББК: 84(7Сое)